The Energy Situation in the Federal Republic of Germany: Analysis of the Current Situation and Perspectives for a Non-Fossil Energy Supply - Atzler, Frank; Türck, Julian; Türck, Ralf; Krahl, Jürgen (Energies (Basel), 2023)
Formulating energy policies at national, European, and global levels is extremely challenging. The move away from fossil fuels is associated with a variety of technological, economic, and social implications, each of which is subject to dynamic changes and societal scrutiny and can hardly be predicted with certainty. Therefore, a fact-based assessment for the path to a sustainable green energy future is sought out in this paper, using the road-based mobility sector of the Federal Republic of Germany as an example. The analysis performed in this paper is built on publicly accessible, reputable sources like DESTATIS and EUROSTAT. In addition, some very simple calculations were made, e.g., on the potential for wind and photovoltaic energy within Germany. Such an analysis needs to start with the overall energy consumption of any one country. A basic assumption of the paper is that the energy system of the future will be based to a large extent on electricity and its storage in chemical energy. It is assumed that, in addition to hydrogen, liquid energy sources will play a significant role due to the simplicity of their logistics and the subsequent implications on cost. Examples of green, electricity-based fuels with great potential are methanol, methane, and ammonia. Additionally, biomass plays an important role, either for direct use as a fuel or as a source of non-fossil carbon. Today, biofuels, i.e., biodiesel and bioethanol, deliver the largest contribution to climate protection in the EU transport sector. The main goal—the reduction of greenhouse gas emissions—often collides with geopolitical circumstances or national political necessities. This includes, for example, the current world market situation and its national impacts caused by the Russian attack on Ukraine. The prospect for a green, sustainable, and defossilized energy supply are discussed in this context. The paper concludes that a defossilized world energy supply and trade based on renewable electricity and its derivatives, eHydrogen and refuels, and on biomass, is feasible.